Light after the dark : a meta-analysis on the effectiveness of grief therapies - Ho, Hui Sze (2016)
This meta-analytic study examined the effectiveness of grief therapies (i.e. cognitive- behavioral therapy (CBT), pharmacotherapy, and group therapy) in alleviating the symptoms associated with an individual who experienced the loss of a loved one (i.e. grief, depression, anxiety, and posttraumatic stress disorder (PTSD) outcomes. Effect sizes from 31 studies (28 journal articles and 3 dissertation studies) were analyzed. Overall, CBT, pharmacotherapy and group therapy were effective in reducing grief, depression, anxiety and PTSD outcomes. CBT was effective in reducing all the four outcomes; pharmacotherapy was effective in reducing grief and depression outcomes; and group therapy was effective in reducing grief, depression, and PTSD outcomes. The following moderators were examined: (a) types of treatment (b) age range of participants (c) recruitment methods (d) duration of loss (e) duration of whole therapy (f) control groups. Limitations of the present study and implications for future research and practice are discussed.